Criminal warranties with circular use and peculiarities of their investigation - Karapetian, Olha; Bilynskyi, Vitalii (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article outlines the advantages and disadvantages of the use and circulation of cryptographic commodities on the basis of which the provision on reduction of corruption risks by means of decentralization of the digital currency is substantiated. Practical approaches to financial investigations of illegally received funds are determined and their main components are substantiated.